Assessment of the perceived effects and management challenges of Mikania micrantha invasion in Chitwan National Park buffer zone community forest, Nepal. Issue 4 (April 2017) - Khadka, Akriti
Abstract: The effects of invasion by Mikania micrantha in the buffer zone of Chitwan National Park (CNP) of Nepal are well documented; however the studies were confined to appraising the perception of household and did not assess the changes in livelihood activities after the invasion. This study presents the effects of invasion of M. micrantha on the livelihood of buffer zone of the Chitwan National Park; hence addressing the gap in information and shows the complex effect of M. micrantha on rural livelihood. The study used a questionnaire survey to 170 households in the CNP of Nepal. The results indicate that the invasion of M. micrantha have negative effects on the community livelihood in the study area. Basic forest products such as fodder and fuel wood have become scarce as a result of reduction in the native plants. Also the spread of M. micrantha is creating impassable copse that destroy wildlife abode and jungle paths resulting into animals to shift their habitat to core area thereby reducing tourism revenues. Therefore, the study concludes that invasion of M. micrantha directly or indirectly is modifying the rural household livelihoods and a quick action is stipulated. Hence, a higher level body like the Ministry of Forestry or Department of National Park and Wildlife Conservation needs to take care of issues related to alien species. Correspondingly, it is also very important that people are aware and educated about alien species and their effects.